Didactic Competence of The Teacher and its Development (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
The article justifies the need to use digital technologies in organizing the didactic process in pedagogical universities. One of the sought-after universal skills of a modern teacher is time management, self-development and self-discipline, the ability to build and implement a trajectory.hexplained in detail in the Aqeedah. From the point of view of the implementation of didactic activities, the importance of professional traininghThe result of education is the acquisition of practical and professional knowledge, self-determination in the digital world, innovative digital services and technologies.hIt is emphasized that there should be dissemination of one's own experience.